Rancang Bangun Sistem Informasi Keuangan Dengan Pendekatan Instrumen Borang Akreditasi - Widiartha, Komang; Dewi, Desak Putu Diah Kumala (INFOTEKS (Information Technology, Computer and Sciences), 2019)
STMIK STIKOM Indonesia, commonly called STIKI, is one of the private tertiary institutions in the field of information technology in Bali with a bachelor level (S1) program. All business processes in support of the academic community are carried out with computers and information systems. From student data management, Kartu Rencana Study (KRS), graduation, library to financial data using a computer system. Management of financial data on STIKI campus is under the responsibility of the Assistant Head II (WK2). Until now, financial management does use a computer system, but is limited to the use of the MS Office Excel application in its management. This has become a problem in the allocation of finance to the preparation of financial reports that lead to forms of study programs and institutions. With these problems will be designed and built a financial information system in the division of Assistant Head II STMIK STIKOM Indonesia that can help accounting staff in managing financial data and simplify the preparation of reports.